Analisis Dampak Program Warung Rakyat Renovasi Terhadap Kesejahteraan Pemilik Warung di Sidoarjo : Studi Kasus pada Warung Kopi Pak Sutopo Hadi - Oktaviani, Adinda Putri Eka; Kusuma, Yanda Bara (Journal of Student Development Informatics Management (JoSDIM), 2024)
In this disruptive era, people tend to have their own enterprises that are often related to UMKM. In Sidoarjo district UMKM growth has experienced a rapid increase. However, in the era of Covid there was a decline so that by 2020 a program of renovation of the people's house was made. This program is being carried out to renovate the community's dining and drinking halls. This study aims to analyze the impact of such programmes on the well-being of individuals, in this study is the farm of Mr. Sutopo Hadi. This study uses qualitative method of correlation. The results of the research showed that the indicators of the program's well-being have been achieved with the happiness perceived by the perpetrators as well as the increased income earned. However, the program has an evaluation of the strengths of its employees, so that the evaluation can improve the program and it can continue.